Isolated boudins or isolated look-like boudins structures? - Rodrigues, Benedito Jesus Gonçalves Calejo (2019)
The difficulties in the identification of boudinated bodies happen whenever isolated or isolated look-like boudins structures occur. Figure shows the criteria for identifying micro and meso structures that could be misunderstand with boudins.